(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2018)
Opioidergic system involves in regulation of sleep and wakefulness. It is possible, therefore, that genetic polymorphisms in OPRM1 influence sleep quality. This study investigated the association of OPRM1 polymorphisms with subjective sleep quality among opioid-naive individuals. This cross-sectional observational study involved 161 opioid-naive males (mean age = 27.74 years; range: 18−63 years). Subjective sleep quality was assessed with the translated and validated Malay version of the Pittsburgh Sleep Quality Index (PSQI). DNA was extracted from whole blood and subjected to polymerase chain reaction (PCR)-genotyping for two OPRM1 polymorphisms (118A>;G and IVS2+691G>;C). Subjects with combined 118A and IVS2+691G alleles (AC haplotype) had significantly lower PSQI scores [mean (SD) = 4.29 (1.76)] compared to those without the haplotype [4.99 (2.50)] (p = 0.004). On the other hand, subjects with combined heterozygous genotype (GC/AG diplotype) had significantly higher PSQI scores compared to those without the diplotype [6.04 (2.48) vs 4.54 (2.22), p = 0.004]. In opioid-naive individuals, AC haplotype and GC/AG diplotype for the 118A>;G and IVS2+691G>;C polymorphisms of OPRM1 are associated with better and poorer sleep quality, respectively.